The association between coronary heart disease and the risk of developing colorectal polyps: insights from the UK Biobank - Geng, Chi; Pang, Ruochong; Xia, Yuqing; Wu, Yong; Zhu, Jianhong; Chen, Yong (Frontiers in Oncology, 2025)
BackgroundWhile numerous risk factors for colorectal polyps (CRPs) have been identified, the impact of coronary heart disease (CHD) on the etiology of CRPs remains ambiguous.MethodsThis investigation involved 424,023 participants from the UK Biobank, with data collected between 2006 and 2010. We utilized Cox regression analysis and subgroup analysis to ascertain risk factors associated with the development of CRPs and to examine the relationship between CRPs and CHD. Propensity score matching (PSM) was employed to address potential confounding variables.ResultsAmong the 424,023 individuals with a history of CHD, the prevalence of colon polyps was 5.6%, while that of rectal polyps was 2.7%. In a longitudinal study with over 12 years of follow-up, Cox regression analysis indicated that CHD constitutes an independent risk factor for the occurrence of CRPs, a conclusion that persisted after adjusting for confounding factors via PSM. Additionally, subgroup analysis revealed that, apart from diabetes mellitus (DM), higher income, moderate physical activity, a nutritious diet, and the use of lipid-lowering medications were associated with favorable outcomes for patients with CHD, as evidenced by hazard ratio (HR) values.ConclusionsThis study establishes a correlation between prolonged CHD duration and an elevated risk of CRPs. In contrast, higher income, moderate physical activity, a nutritious diet, and lipid-lowering medications are protective against CRPs in CHD patients, while DM is a risk factor. These findings support more frequent endoscopic screenings for patients with CHD.